Peran Nilai Personal terhadap Perilaku Pro-lingkungan pada Pendaki Gunung - Kamalia Kamalia (Departement of Mathematics Education, 2024)
Mountaineering in Indonesia is currently a trend among young people and adults. However, a number of environmental problems in the mountains increases with increasing number of mountaineers. A number of studies emphasize the importance of understanding personal values when explaining pro-environmental behavior. This study aims to examine the role of personal values on pro-environmental behavior in mountain climbers. A total of 127 respondents filled out a questionnaire measuring pro-environmental behavior (Dimensions of Behavior and New Ecological Paradigm Scale) and values. In this study, the results showed that there are two personal values that have a role in pro-environmental behavior. The two values are universalism (F=92,35, p<0,05) and power (F=46,33, p<0,05). Furthermore, the result points out that there are differences in pro-environmental behavior among respondents who are members of nature lovers’ group or Kelompok Pecinta Alam (KPA) and non-members of KPA, respondents who have more mountain climbing experience and those who have less experience, and respondents who have previous learning experience and those who do not have previous learning experience.